Determinants of corporate social responsibility: Evidence of manufacturing companies in Indonesia - Tjandra, Ronowati; Setyapurnama, Yudi Santara; Asmara, Eka Noor; Supardi, Supardi; Subagyo, Hasan (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2022)
This study examined the effect of earnings management and the board of directors on corporate social responsibility disclosure. In this study, earnings management is measured using the modified Jones model, while corporate social responsibility disclosure is calculated using the corporate social responsibility disclosure index (CSRI). This study uses the CSRI index based on the Global Reporting Initiative (GRI) reporting standards disclosed by companies in their annual reports. This research was conducted at manufacturing companies listed on the Indonesia Stock Exchange in the 2017-2021 period that met the sample criteria. This research was conducted with a regression analysis model. The results of this study state that earnings management positively influences corporate social responsibility disclosure, and corporate governance proxied by the board of directors negatively affects corporate social responsibility disclosure